Dualistic View in the Formulation of Criminal Offenses in the National Criminal Code - Cahyono, Anton; Vahini Mahiratna, Gusti Ayu Gita Dharma; Mutmainnah, Luluk; Aniqoh, Ihda; Kusuma, Indra Fredika (Hang Tuah Law Journal, 2024)
This article discusses the shift in criminal law perspectives in Indonesia from monist to dualist within the National Criminal Code (KUHP). These reforms were driven by the need for a better criminal legal framework in line with societal developments. The aim of criminal law reform is to achieve legal certainty, justice, and utility. The reasons for reform are influenced by political, sociological, psychological, and practical aspects. Reform efforts include legal discoveries through interpretation, analogy, and legal refinement, covering substantive, structural, and cultural aspects of the law. The National Criminal Code of Indonesia has shifted its perspective from monist to dualist. Monist theory unifies the wrongful nature and culpability as elements of a criminal act, while dualist theory separates them. The National Criminal Code affirms this separation but still formulates the subjective element of negligence in specific criminal acts. This shift in perspective has implications for law enforcement processes in courts. Prosecutors are not required to prove intent, and courts must balance criminal acts and criminal liability. However, there is a need for the development and understanding of these concepts by law enforcement, legal advisors, and judges to maintain a balance between legal certainty and justice. In conclusion, the National Criminal Code adopts a dualist perspective to strengthen the role of criminal law. The separation of criminal acts and criminal liability is expected to enhance the balance between legal certainty and justice in criminal court decisions in Indonesia.